UV-Visible Spectrophotometric Quantification of Diazinon Residues in Brassica juncea L.: Method Development and Validation - Analisa, Mulia Dila; Yeni Maulidah Muflihaha; Indarti, Dwi; AbuBakar, Noor hidayat (Indonesian Chimica Letters, 2026)
Diazinon, an organophosphate pesticide used in agriculture, may leave harmful residues on vegetables. This study determined diazinon residues in green mustard (Brassica juncea L.), optimized extraction solvents, and evaluated spraying intervals before harvest using UV–Visible spectrophotometry as a simple and low-cost method. The novelty lies in developing a validated spectrophotometric approach combined with optimized hexane:acetone extraction (9:1), offering a practical alternative to chromatographic techniques. The method showed excellent linearity (r = 0.999), LOD of 0.018 ppm, LOQ of 0.060 ppm, recovery of 87–108%, and precision with 1.87% RSD. Results indicated that longer spraying intervals reduced residue levels, highlighting the method’s reliability and the importance of proper spraying management.